2004
DOI: 10.1073/pnas.0308657101
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral hemoglobins in Archaea

Abstract: Hemoglobins are ubiquitous in Eukarya and Bacteria but, until now, have not been found in Archaea. A phylogenetic analysis of the recently revealed microbial family of globin-coupled hemebased sensors suggests that these sensors descended from an ancient globin-only progenitor, or a protoglobin (Pgb). Here, we report the discovery and characterization of two Pgbs from the Archaea: ApPgb from the obligately aerobic hyperthermophile Aeropyrum pernix, and MaPgb from the strictly anaerobic methanogen Methanosarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 41 publications
2
89
0
Order By: Relevance
“…Structural studies have shown that heme ligand in Hmp is stabilized by His-85, Tyr-29, and Gln-53 (13). The proximal F8 histidine (His-85 in Salmonella Hmp) in the heme pocket was found to be absolutely conserved in an alignment of 700 vertebrate and nonvertebrate globins and shown to be essential for heme binding in the protoglobin of Aeropyrum pernix (57). In this study an H85A mutation was found to abolish NO⅐ detoxification (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Structural studies have shown that heme ligand in Hmp is stabilized by His-85, Tyr-29, and Gln-53 (13). The proximal F8 histidine (His-85 in Salmonella Hmp) in the heme pocket was found to be absolutely conserved in an alignment of 700 vertebrate and nonvertebrate globins and shown to be essential for heme binding in the protoglobin of Aeropyrum pernix (57). In this study an H85A mutation was found to abolish NO⅐ detoxification (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Specifically, the NAG1 contains the most deeply rooted protoglobin known to date (Supplementary Figure S8), and appears to provide an evolutionary linkage to higher globins such as hemoglobin that are thought to have evolved from an ancestral protoglobin (Moens et al, 1996;Freitas et al, 2005;Nardini et al, 2008). Protoglobins from the obligately aerobic hyperthermophile A. pernix and the strictly anaerobic methanogen Methanosarcina acetivorans have been found to bind molecular oxygen, nitric oxide and CO, potentially protecting the organisms from nitrosative and oxidative stress (Freitas et al, 2004). Consequently, protoglobins have been found in both aerobic and anaerobic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the NAG1 sequence is the most deeply rooted entry of all known globins/protoglobins (Supplementary Figure S8). The protein sequence is related to characterized protoglobins in Aeropyrum pernix, which suggests possible involvement in binding O 2 , CO and NO (Freitas et al, 2004). Other genes encoding proteins for heavy metal detoxification and reduction of oxidative stress are found in the NAG1 assembly and include mercuric reductase (merA), arsenic resistance (arsABC), a superoxide dismutase (sodA) and multiple peroxiredoxins.…”
Section: Functional Analysis Of Nag1 Genome Sequencementioning
confidence: 99%
“…A class of generegulating, chimeric heme proteins, the globin-coupled sensors (GCSs), was discovered in several bacterial groups and an archaean (21). The related single-domain protoglobins (Pgbs) found in archea and bacteria have been proposed to represent the ''ancestral'' globin (22). Here, we report the results of a comprehensive survey of globins.…”
mentioning
confidence: 99%